Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1123/jsm.7.1.25
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for the Analysis of Strategy in Nonprofit Sport Organizations

Abstract: In order to anticipate changes and challenges in their environments, sport organizations must formulate strategies. The purpose of this paper is to develop a framework for the study of strategy formulation in nonprofit sport organizations. Based predominantly on MacMillan's (1983) work on the nonprofit sector, and using Canadian national sport organizations as an illustration, this study identified several strategic imperatives to uncover the types of strategies that could be undertaken by nonprofit sport orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 8 publications
0
56
0
2
Order By: Relevance
“…In line with Frambach and Schillewaert (2002), Newell and Swan (1995) and Thibault, Slack and Hinings (1993), the competitive environment these sports federations perceive might stimulate service innovation implementation. We assume a highly perceived regional competitive environment, together with high staff involvement and positive attitudes regarding change and newness favour service innovation in sports federations.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…In line with Frambach and Schillewaert (2002), Newell and Swan (1995) and Thibault, Slack and Hinings (1993), the competitive environment these sports federations perceive might stimulate service innovation implementation. We assume a highly perceived regional competitive environment, together with high staff involvement and positive attitudes regarding change and newness favour service innovation in sports federations.…”
Section: Discussionmentioning
confidence: 90%
“…Thibault, Slack, and Hinings (1993) suggested that sports federations innovate in response to the competitive position of their sport in order to increase their program attractiveness to (new) members. Competitive and environmental pressures perceived by sports federations might stimulate change (Caza, 2000).…”
Section: Sports Federations' Service Innovationmentioning
confidence: 99%
See 3 more Smart Citations